Strategic interviewing : how to hire good people - Camp, Richaurd R. (University of Michigan Business School management series., 2001)
Interviewing is one of the most effective ways to identify and attract employees who will be successful enough to stay. But few managers are adept at the skill. This book helps eliminate expensive errors of judgment by presenting readers with a set of behaviorally based interviewing strategies. Written by the faculty of the prestigious University of Michigan Executive Education Center - and based on one of their most popular courses - its seven-step 'Strategic Interviewing Approach' helps interviewers define the competencies candidates need to possess and make hiring decisions based on accurat.